Study of heat transfer in porous inserts - Chiem, Terence Kok Siong. (2011)
This research project explores the use of porous inserts for heat transfer enhancement in recirculating flows. The first test case is on flow inside cavities and over a backward-facing step under both steady and unsteady state conditions. The second case is a vertical inlet channel flow where the inlet and outlets are 90 degree to each other. This is a new flow phenomenon ever studied.